A mother's legacy: the strength of maternal effects in animal populations. (29th July 2019) - Moore, Michael P.; Whiteman, Howard H.; Martin, Ryan A.
Abstract: Although mothers influence the traits of their offspring in many ways beyond the transmission of genes, it remains unclear how important such 'maternal effects' are to phenotypic differences among individuals. Synthesizing estimates derived from detailed pedigrees, we evaluated the amount of phenotypic variation determined by maternal effects in animal populations. Maternal effects account for half as much phenotypic variation within populations as do additive genetic effects. Maternal effects most greatly affect morphology and phenology but, surprisingly, are not stronger in species with prolonged maternal care than in species without. While maternal effects influence juvenile traits more than adult traits on average, they do not decline across ontogeny for behaviour or physiology, and they do not weaken across the life cycle in species without maternal care. These findings underscore maternal effects as an important source of phenotypic variation and emphasise their potential to affect many ecological and evolutionary processes.